Happiness of Nursing Students of Faculty of Nursing, Chaiyaphum Rajabhat University - Tongsawang, Kamonrut (Journal of The Royal Thai Army Nurses, 2022)
This research is a descriptive research. The objectives are as follows: 1) to study the happiness level of Nursing Students of Faculty of Nursing, Chaiyaphum Rajabhat University, 2) to compare happiness levels of nursing students Classified by grade level 3) to study factors related to happiness of Nursing Students of Faculty of Nursing, Chaiyaphum Rajabhat University. The sample group was Nursing Students of Faculty of Nursing, Chaiyaphum Rajabhat Universit, Academic Year 2018, consisted of 359 people. and a questionnaire on the Happiness Index (TMHI - 55) of the Department of Mental Health. It is a 4-level rating scale with 55 items to determine the confidence. Using Cronbach’s alpha coefficient, the value 0.984. The statistics used were descriptive statistics, one-way ANOVA and Chi-Square. The results showed that happiness of Nursing Students of Faculty of Nursing, overall, found that the happiness level was lower than the general population of 352 ( 98.05 percent ) and the happiness level was the same as that of the general population of 7 people (1.94%). Year 1 had the highest average happiness level was 124.95 and the year of study correlated with happiness of Nursing Students of Faculty of Nursing, Chaiyaphum Rajabhat University with statistical significance at the .05 level. can lead to Basic information for planning, organizing activities, teaching and learning to encourage students to be happy in study life.